Women through the eyes of men a descriptive study on the perception and attitude of men toward their female colleagues in the mass media. - Velarde, Gretchen G. (no date found)
This descriptive research aimed to find if men working in gthe mass media still expect women to embody stereotypic feminine trits and if their attitude toward trheir female colleagues are still based on their stereotypical perception of women. This research employed 30 respondents from six news outfits operating within the islands of Panay. Five respondents were taken from each news outfit and each medium (television, radio and print) was repreented by two news outfit. Thus, GMA and ABS-CBN for the television medium, Aksyon Radio and RMN for the radio medium, and the News Today and Panay News for the print medium. The result of the research showed that men working in the mass media expect women to embody stereotypic feminine traits; the most preferred is the naturally caring trait where 23 respodnents chose the said trait. In the attitude toward women colleagues in the amss media, most of the answers on items of the second part of the survey show thatmen are still stereotupical in their attitude toward their female collegues. Hence, men working in the mass media are in dire need for seminars and trainings that gear toward a more egalitarian perception toward women in genral and an eglitarian working relationship with their women collegues in the news media.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Women -- Mass Media